Dogon identity in mask songs : the dama of tabanongou - (:unkn) unknown (My University, 2025)
The peoples of black Africa are confronted with the phenomenon of loss of identity. Recognized for its culture and values of yesteryear, Dogon society tends to lose its bearings because of globalization, social, environmental and religious changes. However, it is of advantageous importance to safeguard certain values that define our society to ensure the political, economic and social development of the continent. How can we envisage a stable and independent African society without its identity values? Thus, through this study, we have chosen to discover a Dogon identity by focusing on a societal, religious and cultural practice. This study aims to highlight the implications of mask chants and funerary rites as integral parts of the broad process of construction and affirmation of the Dogon people. It aims to collect part of the literature of masks from the Tabanongou sector for the discovery of social identity. Field ethnography and textual content analysis serve as a methodological approach.
Keywords: African Research